2020
DOI: 10.3390/data5040108
|View full text |Cite
|
Sign up to set email alerts
|

Dataset of User Reactions When Filling Out Web Questionnaires

Abstract: This paper presents the dataset and the results of the analysis of user reactions when filling out questionnaires. Based on the analysis of 1980 results of users’ responses to simple questionnaire questions, patterns in user reactions were revealed. Data analysis shows that a user is characterized by reactions when answering a variety of questions, reflecting the individual skills of the interface, reading speed, speed of choosing an answer, which can be used to supplement personal verification in information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Technically, user reaction time is the timespan from the start of the web survey screen representing a page with a number of questions to the time when the user clicked the desired answer option. In works [4][5][6] on various experiments with large samples, it was shown that reaction time reflects personal skills of interaction with the user interface. Of course, various factors may influence the change in reaction time, but in general, reactions are maintained the same over the course of a few hours of experimentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technically, user reaction time is the timespan from the start of the web survey screen representing a page with a number of questions to the time when the user clicked the desired answer option. In works [4][5][6] on various experiments with large samples, it was shown that reaction time reflects personal skills of interaction with the user interface. Of course, various factors may influence the change in reaction time, but in general, reactions are maintained the same over the course of a few hours of experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…Different researchers [31][32][33][34] defined and filtered random clickers and their thoughtless responses in different ways. In previous studies of web surveys [4,5,30], we gained experience in detecting random clickers. In this study, we simulate the behavior of random clickers based on the analysis of data from previous surveys when working with the given web interface.…”
mentioning
confidence: 99%